Pengaruh Penyimpanan Jangka Panjang (Long Term) terhadap Viabilitas dan Vigor Empat Galur Benih Inbred Jangung - Kartahadimaja, Jaenudin; Syuriani, Eka Erlinda; Hakim, Nurman Abdul (Politeknik Negeri Lampung., 2013)
Seed corn are orthodox seeds quite resistant to drying and low temperature storage. On optimal storage conditions, will be able to orthodox seeds stored for several years. Quickly so as not to extinction, maize inbred strains that have been generated assemblies Polinela painstakingly preserved. The research objective was to determine whether the strain of inbred corn seed stored in the Col storage at a temperature of 3°C - 5°C for more than 4 years of viability and vigor still good? The experiment was conducted at the Polytechnic of Lampung November to December 2012. Research using completely randomized design, consisting of 4 strains of inbred seed corn that had been stored for 4 years in cold storage as treatments. Tests conducted in the laboratory and field. Each treatment was repeated four times. Data were analyzed by analysis of variance, if there is a difference between the treatments, the data were further tested by LSD test at 5% significance level. Parameters observed 1) Number of normal seedlings, 2) number of abnormal sprouts, 3) seed that dies, 4) The percentage of germination, 5) Sprouts Normal Form, 6) form abnormal sprouts. The results showed: 1) maize inbred lines seed storage Polinela assemblies under conditions of water content of seeds stored at 10% which is placed in cold storage temperature of 3 ° C - 5 ° C for 4 years, is able to maintain the viability and vigor of seeds to remain above 80%, 2) Viability seeds were tested in the laboratory is still above 96.0%, while the seed vigor test results in the field of more than 93.0%. Keywords: corn inbred strains, long term Storage